2019
DOI: 10.1101/633271
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disentangling neuronal inhibition and inhibitory pathways in the lateral habenula

Abstract: 22 Phone: +44 (0)141 548 2122 23 24 2 25 Summary: The lateral habenula receives inhibitory input from three distinct sources: 26 from local PV-positive neurons, from PV-positive neurons in the medial dorsal thalamic 27 nucleus (MDT); and from SOM-positive neurons in the ventral pallidum (VP). 28 3 Abstract 29 The lateral habenula (LHb) is hyperactive in depression, and thus potentiating 30 inhibition of this structure makes an interesting target for future antidepressant 31 therapies. However, the circuit mech… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Several reports have recently proposed the existence of locally targeting GABAergic neurons within the LHb (Flanigan et al., 2020; Webster et al., 2020; Zhang et al., 2018). Earlier work has also indicated that a subclass of neuron physiologically and morphologically akin to that of neurogliaform cells exists within the LHb (Wagner et al., 2016; Weiss & Veh, 2011), although as‐of‐yet no evidence exists to indicate that these form functional local connections.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have recently proposed the existence of locally targeting GABAergic neurons within the LHb (Flanigan et al., 2020; Webster et al., 2020; Zhang et al., 2018). Earlier work has also indicated that a subclass of neuron physiologically and morphologically akin to that of neurogliaform cells exists within the LHb (Wagner et al., 2016; Weiss & Veh, 2011), although as‐of‐yet no evidence exists to indicate that these form functional local connections.…”
Section: Introductionmentioning
confidence: 99%
“…Although about 80% of PV neurons in the lateral habenula were surrounded by PNNs (Appendix 1, Figure S1F and G), more than 40% are GABA-negative and express little GAD1 and GAD2 (Appendix 1, Figure S1C, D, E and G). Webster and colleagues 35 have reported finding GABApositive and glutamatergic PV neurons, whose optogenetic activation elicited inhibitory and excitatory responses in the lateral habenula. That study and the present study showed that PV neurons in the lateral habenula are a heterogeneous population consisting of GABAergic and glutamatergic neurons; therefore, the roles of the PV neurons in the lateral habenula are thought to be different from in the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…This study contains some limitations. Although LHb neurons are predominantly glutamatergic [40], a small subset express glutamic acid decarboxylase 2 [41][42][43], which is recognized as a GABA marker. Neurons in the LHb respond differently to the activation of LHA glutamatergic neurons [16].…”
Section: Discussionmentioning
confidence: 99%